A Study of Drug Interaction with Nifedipine and Magnesium Sulfate in the Management of Preeclampsia: An Observational Study - Awaluddin, Nurhikma; Aadilah, Aadilah; Mahasakti, M Tri Budi (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Maternal mortality rate (MMR) remains a major priority in global health. The World Health Organization (WHO) estimates that MMR will decrease to 70 per 100,000 live births by 2030. However, in 2015, MMR in Indonesia reached 305 per 100,000 live births. Drug Related Problems (DRPs) are undesirable events that occur due to drug therapy and can hinder the recovery process of patients. Identifying drug-related issues during treatment is crucial for reducing morbidity, mortality, and therapy costs, as well as enhancing the effectiveness of pharmacological therapy.vThis study aims to identify DRPs caused by the use of the combination of Nifedipine and Magnesium Sulfate in preeclamptic patients at RSIA Sitti Khadijah 1 Makassar. The research method employed is non-experimental (observational) with a descriptive (qualitative) approach. The results indicate that among 32 preeclamptic patients who consumed the combination of Nifedipine and Magnesium Sulfate, there were no reported DRPs or adverse effects that jeopardized the patients' lives. These findings suggest that the combination therapy is in accordance with the management guidelines for preeclampsia in pregnant women based on national medical service protocols.